Presenting the model of portfolio management in investment funds based on behavioral financial variables - Seyed Mohammad Hadi Shahamat; Mahdi Mohammad Bagheri; Ali Raispour Rajabali; Mohsen Zayandeh Roudi (ارزش آفرینی در مدیریت کسب و کار)
Abstract The purpose of this research is to present a model of portfolio management in investment funds based on behavioral financial variables. The method of this research was applicable in terms of purpose, and of descriptive-survey type. The statistical population of the research includes 10 experts who have a PhD. degree in financial management or accounting and university professors. The method of data collection was a researcher-made questionnaire and analyzed using structural and interpretive modeling. The results showed that in the first level, the most effective components included: control of the fear of surviving profit, normalization of conservative behaviors, and control of regret-avoidance behaviors. In the second level, the components influencing the first level, i.e. paying attention to self-control behaviors, having a written investment strategy, paying attention to the principles of mental accounting; and in the third level, the components influencing the second level, which include behavioral optimism and pessimism, Paying attention to risk-averse and risk-taking behaviors and, controlling mass behaviors; and the most effective component at the fourth level includes the effect of inclination. In the Mik Mak model, most of the variables were also included in the linked variables, which have a strong influence and also a strong dependence force. Extended Abstract Introduction The behavior of investors as those who seek to optimize profit, omniscient, and infinitely rational, is difficult to understand in the real world. Even assuming that investors are aware of everything, the fact that they may have to interact in information search processes and that they may have rational limitations has been ignored (Barasud & Zamardian, 2019). The uncertainty in analyzing investment risk against expected market returns means that portfolio management has been a thoughtful challenge for portfolio managers. Fund managers should change their portfolios at regular intervals and should add a tendency style. Portfolio management is the allocation of assets, diversification and rebalancing of assets up to higher than the limit set. Asset allocation is the division of assets in the portfolio between risky and risk-free asset classes. Typically, investing requires the careful design of an investment policy statement that appeals to the unique needs of investors. Diversification is sharing risk and reward across asset classes because it is difficult to determine which particular subset of assets is likely to perform better than another. Therefore, diversification is a process of expanding the number of assets in a portfolio in order to minimize investment risk (Doeh Agblobi et al, 2020). Thus, in this research, the researcher intends to answer the basic question: what is the model of portfolio management in investment funds based on behavioral financial variables? Theoretical Framework Portfolio management Portfolio management is the art and science of deciding on investment texture and strategy, matching investments with objectives, allocating assets to individuals and institutions, and balancing risk against performance (Bkhit, 2019). Behavioral finance Behavioral finance studies how psychological phenomena affect financial behavior. Financial behavior studies how people behave in determining financial matters. Behavioral finance is a new theoretical branch in finance that is defined by combining the knowledge of psychology, sociology and other social sciences (Meisa Dai et al, 2021). Investment funds On the other hand, in most of the developed countries, investment funds are considered as the central core of the capital market and they direct huge amounts of wandering capital to the productive and active sectors of the society every month. By adopting appropriate policies, these funds can play an essential role in reducing inflation, increasing production, and improving the efficiency of managers. Fortunately, the investment funds industry in Iran was established in 2007 with a delay of several decades, but with a lot of acceptance from the investors. Considering the irreplaceable role of these funds in allocating optimal financial resources in the capital market, evaluating the type of transactions in these companies and the effect of their type of ownership on the type of transactions of these financial intermediaries can provide valuable information to investors (Shams & Esfandiari Moghadam, 2016). Bennett et al, (2023) mentioned that it was implemented as a behavioral finance approach for pricing decentralized financial assets. They found that decentralized finance provides a better explanation of asset pricing in rapidly evolving markets than traditional financial theory. Investor attention, sentiment, discoveries and biases, and network effects interact to form a highly volatile and dynamic market. Keshavarz et al, (2021) in a research on investment strategies based on technical indicators: evidence of behavioral reactions of investors in the Tehran Stock Exchange. The results showed that according to the coefficient of variation and the correlation test, the results indicate that the indicators of moving average, exponential moving average, and relative power, compared to other indicators, are more indicative of the behavioral reactions of investors. Research methodology The method of this research was applicable in terms of purpose, and of descriptive-survey type. The statistical population of the research includes 10 experts who have a PhD. degree in financial management or accounting and university professors. The method of data collection was a researcher-made questionnaire. Research findings Data analysis using structural and interpretive modeling. The results showed that in the first level, the most effective components included: control of the fear of surviving profit, normalization of conservative behaviors, and control of regret-avoidance behaviors. In the second level, the components influencing the first level, i.e. paying attention to self-control behaviors, having a written investment strategy, paying attention to the principles of mental accounting; and in the third level, the components influencing the second level, which include behavioral optimism and pessimism, Paying attention to risk-averse and risk-taking behaviors and, controlling mass behaviors; and the most effective component at the fourth level includes the effect of inclination. In the Mik Mak model, most of the variables were also included in the linked variables, which have a strong influence and also a strong dependence force. Conclusion The present research was conducted by presenting the model of portfolio management in investment funds based on behavioral financial variables. The results obtained in this research is aligned and in the same direction with the results of Bennett et al, (2023), Fuladi et al, (2021), Keshavarz et al, (2021), Sajid (2021), Leković (2020), Lotfolah Hamdani (2020) and Asadi Qarajalo & Abdo Tabrizi (2019). Bennett et al, (2023) mentioned that it was implemented as a behavioral finance approach for pricing decentralized financial assets. They found that decentralized finance provides a better explanation of asset pricing in rapidly evolving markets than traditional financial theory. Investor attention, sentiment, discoveries and biases, and network effects interact to form a highly volatile and dynamic market. Therefore, it is suggested to investigate the effects between these variables using structural equation models in future researches. Also, other methods of uncertainty modeling, including fuzzy DEA, should be used to model these indicators.